patient care, quality of nursing Hubungan Pelayanan Pasien terhadap Mutu Pelayanan Keperawatan Selama Masa Pandemi COVID-19 di Puskesmas Meo-Meo Kota Baubau: Relationship Patient Service to Quality of Nursing Services During COVID-19 Pandemic at Meo-Meo Health Center - agus darmawan (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Background: Puskesmas which is spearhead in breaking of transmission COVID-19, needs to make efforts prevent and transmit infection. Objectives: Purpose study was to determine relationship between patient care in form reliability, responsiveness, assurance, empathy, direct evidence quality nursing services during COVID-19 pandemic. Research Metodes: Type research used is cross sectional study. Population were all outpatients who came for treatment as many as 1681 people, sample was 95 people and side method used was purposive sampling. Analysis used was univariate analysis and bivariate analysis at 95% confidence (a = 0,05). Results: Results showed that reliability relationship had ρ=0,000<α=0,05, responsiveness relationship had ρ=0,002<α=0,05, assurance relationship had a ρ=0,007<α=0,05, empathy relationship had ρ=0,001<α=0,05, direct evidence relationship has ρ=0,000<α=0,05 to quality of nursing services during COVID-19 pandemic. Conclusion: Conclusion shows that is a relationship between patient care and quality of nursing services during COVID-19 pandemic at Meo-Meo Health Center